Peran Pemerintah Jerman dalam Menangani Pengungsi Asal Suriah Sebagai Tenaga Kerja di Jerman Pasca Open Door Policy - Nisa, Hasri Maghfirotin (Global and Policy Journal of International Relations, 2020)
ABSTRACTIn 2013 to 2015, Syrian Refugees came and tops the list of Germany with an influx of 950.827 people. 1.164.269 asylum applications were first filed in 2015 (441.899) and in 2016 (722.370), besides the open-door policy (a large wave of refugees in Germany). On the other hand, refugees are required to pay taxes, but jobs for refugees are still rarely, with the majority of refugees from Syria lacking in skills, language, and important documents. The study aims to find out how the German government plays a role in handling Syrian Refugees as a labor in post-open door policy in Germany. Researchers used the concept of national interest by Thomas Hobbes as well as the role of state by K. J. Holsti (1992). The research methodology used a qualitative description with the release of data through literature review and literature studies originated from official websites published by Economic Cooperation and Development, International Labour Organization in 2013-2017, and others. The study explained that the German Government established and implemented policies for Syrian refugees were expanding jobs for refugees, document redeployment, and skill training.Keywords: Syrian Refugees, Labor Problems, German GovernmentPada tahun 2013 sampai 2015 Pengungsi Asal Suriah menempati posisi teratas di Jerman dengan jumlah pengungsi yang masuk 950,827 jiwa. Sebanyak 1.164.269 aplikasi suaka pertama kali diajukan selama 2015 (441.899) dan 2016 (722.370), hal itu bersamaan dengan kebijakaan pintu terbuka (gelombang besar pengungsi di Jerman). Di sisi lain, pengungsi diharuskan membayar pajak oleh Pemerintah Jerman, namun lowongan pekerjaan untuk pengungsi masih jarang dijumpai, mayoritas pengungsi asal Suriah kurang memiliki keterampilan skill, bahasa, serta dokumen-dokumen penting. Penelitian ini bertujuan untuk mengetahui Bagaimana Peran Pemerintah Jerman Dalam Menangani Pengungsi Asal Suriah Sebagai Tenaga Kerja Di Jerman Pasca Open Door Policy. Peneliti menggunakan konsep kepentingan nasional oleh Thomas Hobbes serta konsep peranan negara oleh K.J Holsti (1992). Penelitian ini menggunakan pendekatan deskripsi kualitatif dengan dengan pengambilan data melalui literature review dan studi pustaka yang berasal dari website resmi Organisation for Economic Cooperation and Development, International Labour Organisation, UNHCR tahun 2013-2017 dan lainnya. Hasil penelitian ini menjelaskan bahwa Pemerintah Jerman membuat dan menerapkan kebijakan untuk pengungsi asal Suriah seperti memperluas lapangan pekerjaan untuk pengungsi, pemudahan dokumen, dan pelatihan skill.Kata-Kata Kunci : Pengungsi Asal Suriah, Masalah Tenaga Kerja, Pemerintah Jerman